The Impact of Pain and Other Symptoms on Quality of Life in Women With Relapsing-Remitting Multiple Sclerosis - Newland, Pamela K. (2009)
The purpose of this study was to assess pain, fatigue, depression, sleep disturbance, and quality of life (QOL) in women with relapsing-remitting multiple sclerosis (RRMS) compared with healthy controls. A prospective, cross-sectional, matched-control study was conducted in women with RRMS compared with healthy women. Compared with healthy women, women with RRMS had (a) greater pain presence over 7 days (67%), (b) higher pain intensity, and (c) more pain interference. Pain had a negative impact on fatigue, depression, and sleep in both groups. In all participants, fatigue, depression, and sleep disturbance contributed to decreased mental QOL (mental component summary of QOL scores). Pain has significant nursing implications for women with RRMS. Pain often occurs in association with fatigue, depression, and sleep disturbance, which can lead to a decreased mental QOL.